EFFECT OF RECENTRIFUGATION ON THE LEVELS OF HIGH SENSITIVITY TROPONIN I - Nida, Sumbal; Afzal, Raja Kamran; Saeed, Mohammed Zaheer Us (Pakistan Armed Forces Medical Journal, 2018)
Objective: To compare the levels of high sensitivity troponin I in plasma after specimen re-centrifugation in patients presenting with acute coronary syndrome.Study Design: Cross sectional study.Place and Duration of study: Department of Pathology, Armed Forces Institute of Cardiology, Rawalpindi, from Sep to Nov 2017.Material and Methods: Seventy five patients’ plasma samples of high sensitivity troponin I levels, exceeding the value of 0.06ng/ml were analyzed. Blood was collected in K/EDTA evacuated tubes and plasma was separated after an initial centrifugation (2000 g, 10 min; not refrigerated). The samples were recentrifuged after first analysis. High sensitivity troponin I was measured through the chemiluminescence technique on ADVIA CENTAUR XP immunoassay analyzer. Normally distributed continuous variables were presented as Mean ± SD and the others as median. Two-tailed Wilcoxon analysis was applied to determine the difference in high sensitivity troponin I specimens before and after recentrifugation. A p-value